Suplemento alimentar, em forma de tablete, à base de camarão liofilizado e ingredientes funcionais - Guilherme, Daniele Duarte (2016)
The fish consumption should be stimulated for its nutritional value and also constitute a healthy with functional ingredients needed to nourish the body, in all age groups. This work aimed to use the marine shrimp (Litopenaeus vannamei), one of the most consumed species and cultivated in the Brazilian Northeast, in the development of a functional supplement in a tablet the basic protein concentrate obtained from shrimp lyophilized form and inserting functional of ingredients, resulting in a product with high protein and functional, important constituents in the nutrition and health of human beings, especially for practitioners of sports activities. The tablets were formulated with shrimp lyophilized protein concentrate, added quinoa, flaxseed, oats and oil omega 3 and evaluated for 90 days of storage, at room temperature, as the chemical components (moisture, protein, lipids, ash), fatty acids, pH, water activity (Aw), rancid (TBARS), microbiological analysis (Coliform 45 ° C, Staphylococcus coagulase positive, Salmonella sp. and Bacillus cereus) and the sensorial quality. The tablets showed microbiological and physico-chemical results consistent with the law. The pH values and TBARS have varied depending on formulation and the packaging, while remaining within acceptable limits until 90 days of storage at ambient temperature. Regarding the profile of fatty acids, they showed high levels of essential fatty acids. As for sensory analysis F02 formulation it showed the preference, better purchase intent and greater acceptability for the parameters (flavor, aroma, texture and overall impression) evaluated which have remained stable with no significant differences between the storage periods investigated, can be attributed to the type of packaging the same, which was laminated, while the other formulations suffered packaging in transparent flexible packaging. Thus, F02 product appeared as a product of high nutritional value, containing promoters ingredients of functional properties in order to attend the demand for specific diets, consumers who prioritize the nutritional quality and practicality food to be consumed.